Unilateral synchronous masses of the neck revealing a malignant Carotid Body Tumor: A case report and literature review. (April 2023) - Sallom, Mostafa; Al Laham, Omar; Ghannam, Eman; Ghannam, Mohammad; Mohammad, Ammar
Abstract: Introduction and importance: Paraganglioma (PG); also known as Glomus Tumor, is a rare neoplastic entity that originates from neural crest cells. It can manifest in different patterns, chiefly benign but others are locally invasive and malignant in behavior. Due to the prevalence of other more common types of neck masses and Paraganglioma's exceeding rarity, misdiagnoses can easily take place, and this results in higher patient morbidity and mortality rates. Preoperative diagnosis constitutes a major clinical challenge, especially in patients with a previous surgical history in the neck region like our patient. Case presentation: We are hereby presenting the case of a 56-year-old female with a known history of total thyroidectomy, who presented to our department with a progressively growing painful recurring neck mass two years following her total thyroidectomy. The preoperative diagnostic assessment revealed two unilateral synchronous masses encapsulating the Right Common Carotid Artery and occupying the common carotid bifurcation. Clinical discussion: Complete surgical resection of the lesions after isolation from the surrounding anatomical structures was done. Subsequent histopathological and immunohistochemical analyses of the specimens established the diagnosis of a Carotid Body Tumor (CBT). Conclusion: CBTs are rare vascular neoplasia, and they possess the potential for malignant transformation. This neoplasia warrants investigation and documentation to establish innovative diagnostic parameters and accomplish timely surgical interventions. To the best of our knowledge, this is the first documented case of a unilateral synchronous malignant Carotid Body Tumor from Syria. Surgery remains the treatment of choice, while radio-/chemotherapy is reserved for non-surgical cases only. Highlights: Paragangliomas are extremely rare tumors and comprise less than 0.012 % of all human neoplasia. Paragangliomas do not constitute more than 0.6 % of all presenting neck masses. Synchronous unilateral PGs are even rarer. CBTs comprise 6–10 % of malignant neck masses. Early diagnosis facilitates treatment and minimizes potential complications. Definitive diagnosis is reached via histopathology accompanied with immunohistochemical analysis. Surgical resection is the treatment of choice for Carotid Body Tumors while radiotherapy is reserved for inoperable cases.